Association of pharmacokinetic and metabolic parameters derived using simultaneous PET/MRI: Initial findings and impact on response evaluation in breast cancer. Issue 92 (July 2017) - Jena, Amarnath; Taneja, Sangeeta; Singh, Aru; Negi, Pradeep; Mehta, Shashi Bhushan; Ahuja, Aashim; Singhal, Manish; Sarin, Ramesh
Highlights: Simultaneous PET/MRI for the association between pharmacokinetic and metabolic parameters in breast cancer patients. Correlation of these acquired parameters biologically in the milieu of the tumor may be used in prognostication. Potential of simultaneity of pharmacokinetic and metabolic parameter in breast cancer for assessing response to therapy. Abstract: Purpose: To study relationships among pharmacokinetic and 18 F-fluorodeoxyglucose ( 18 F-FDG) PET parameters obtained through simultaneous PET/MRI in breast cancer patients and evaluate their combined potential for response evaluation. Methods: The study included 41 breast cancer patients for correlation study and 9 patients (pre and post therapy) for response evaluation. All patients underwent simultaneous PET/MRI with dedicated breast imaging. Pharmacokinetic parameters and PET parameters for tumor were derived using an in- house developed and vendor provided softwares respectively. Relationships between SUV and pharmacokinetic parameters and clinical as well as histopathologic parameters were evaluated using Spearman correlation analysis. Response to chemotherapy was derived as percentage reduction in size and in parameters post therapy. Results: Significant correlations were observed between SUVmean, max, peak, TLG with K trans (ρ = 0.446, 0.417, 0.491, 0.430; p ≤ 0.01); with Kep(ρ = 0.303, ρ = 0.315, ρ = 0.319; p ≤ 0.05); and with iAUC(ρ = 0.401, ρ = 0.410, ρ = 0.379; p ≤ 0.05, p ≤ 0.01). The ratio of ve/iAUC showed significant negative correlation to SUVmean, max, peak and TLG (ρ = 0.420, 0.446, 0.443, 0.426; p ≤ 0.01). Ability of SUV as well as pharmacokinetic parameters to predict response to therapy matched the RECIST criteria in 9 out of 11 lesions in 9 patients. Maximum post therapy quantitative reduction was observed in SUVpeak, TLG and K trans . Conclusion: Simultaneous PET/MRI enables illustration of close interactions between glucose metabolism and pharmacokinetic parameters in breast cancer patients and potential of their simultaneity in response assessment to therapy.